Medicinal Plant for Curing Alzheimer’s Disease - Singh, AK (International Journal of Pharmaceutical & Biological Archive, 2010)
Neurodegenerative diseases of the human brain comprise a variety of disorders that affect an increasing percentage of the population. Some of these are age dependent (e.g. Alzheimer’s and Parkinson’s diseases) and some are infection dependent, e.g. human immunodeficiency virus (HIV/AIDS). Alzheimer’s disease (AD) is a complex, multifactorial, heterogeneous mental illness, which is characterized by an age-dependent loss of memory and an impairment of multiple cognitive functions. It is the most common type of dementia in the ageing population due to a severe loss of cholinergic neurons in selected brain area. In traditional practices of Ayurvedic and Chinese medicine, numerous plants have been used to treat cognitive disorders, including neurodegenerative diseases such as Alzheimer’s disease. An ethno-pharmacological approach has provided leads to identifying potential new drugs from plant sources, including those for cognitive disorders. Herbal remedies that have demonstrable anti-alzheimer activities have provided a potential to psychiatric pharmaceuticals and deserve increased attention in future studies. This article reviews different plants and their active constituents that have been used in traditional Ayurvedic medicine and for their reputed cognitive-enhancing or anti-ageing effects.